Dichotomy in Hedgehog Signaling between Human Healthy Vessel and Atherosclerotic Plaques - Queiroz, Karla C S (ScholarOne, 2012)
The major cause for plaque instability in atherosclerotic disease is neoangiogenic revascularization, but the factors controlling this process remain only partly understood. Hedgehog (HH) is a morphogen with important functions in revascularization, but its function in human healthy vessel biology as well as in atherosclerotic plaques has not been well investigated. Hence, we determined the status of HH pathway activity both in healthy vessels and atherosclerotic plaques. A series of 10 healthy organ donor–derived human vessels, 17 coronary atherosclerotic plaques and 24 atherosclerotic carotid plaques were investigated for HH pathway activity. We show that a healthy vessel is characterized by a high level of HH pathway activity but that atherosclerotic plaques are devoid of HH signaling despite the presence of HH ligand in these pathological structures. Thus, a dichotomy between healthy vessels and atherosclerotic plaques with respect to the activation status of the HH pathway exists, and it is tempting to suggest that downregulation of HH signaling contributes to long-term plaque stability.